Analysis of Mutual Interaction Effect of Six-Individual Characteristic Factors of Safe Weight Lift Model - Muyiwa, Omotunde; Akanbi, Olusegun (INSTEP Network, 2023)
An ergonomic mathematical model to compute Safe Weight Lift (SWL) was formed with principle of strain energy to limit risk of low back pain amid construction employees in Nigeria. However, mutual interaction effect of the selected factors were not yet studied. Therefore, analysis of mutual interaction effect of compounded chosen male distinctive factors of biomechanical of body weight, spinal shrinkage, and spine length, with physiological of age, and gender also, psychophysical of surrounding temperature and lift frequency were done. The factors data were gotten using ZT-160 scale, tailor-tape rule, fly-back timing and RH/Temperature pen from fifty masculine manual construction workers selected using purposive sampling technique. The data were inputted into Ms Excel and SPSS for analyses using Multiple Linear Regression (MLR), Regression Curve Estimate (RCE), and ANOVA at alpha level 0.05. The MLR investigation shown that mutual interactions of the compounded factors were significant (p=0.00) and gave R2=0.94, while RCE predicted quadratic relationship with the SWL (p=0.00), and the ANOVA revealed that factors were significant (p=0.00) with F-test=404.53. The mutual interactions of the model selected factors were significant. Therefore, it can be used as a tool for decision-making for safety management of male labourers involve in manual load handling.